FORMULASI MATERIALITAS : STUDI PADA KANTOR AKUNTAN PUBLIK DI INDONESIA - Yustrida Bernawati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2016)
Materiality is an important concept in accounting and auditing practices that should be applied by accountants in performing their duties. To date, there are no guidance or directions that can be used to accommodate all the needs of accountants to make decisions regarding materiality so that accountants should be able to formulate materiality using professional skills acquired through experience or education. This study aims to know the various quantitative and qualitative factors areconsidered by accountants to formulate materiality and determine whether there is a difference in considering these factors based on experience and the type of Public Accountant Firms. Data were collected by questionnaires distributed to the partners of the Public Accountant Firm in Indonesia. Testing by using Principal Component Analysis (PCA), Kolmogorov-Smirnov test and Kruskal-Wallis Analysis of varience of Ranks. The results showed that the accountant uses many factors considered in the formulation of materiality and in general differ in using a number of quantitative factors, but did not differ in the use of the many qualitative factors. This suggests that consideration of materiality is a qualitative judgement but it must be defined in quantitative form. This study contributes to the development of auditing and accounting practices and as an input for decision makers to formulate quantitative materiality in accounting and auditing practice.